2011
DOI: 10.2166/wst.2011.201
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced reduction of excess sludge and nutrient removal in a pilot-scale A2O-MBR-TAD system

Abstract: In this study, a pilot scale anaerobic-anoxic-oxic (A2O) process with submerged membrane (MBR) in the oxic tank was coupled with thermophilic aerobic digestion (TAD) reactor and was operated for longer than 600 days to treat real domestic wastewater. Regardless of the varying conditions of the system, the A2O-MBR-TAD process removed MLSS, TCOD, BOD, TN, TP, and E. coli about 99%, 96%, 96%, 70%, 83%, and 99%, respectively. The additional TP removal of the system was due to the precipitating agent directly added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…So far, chemical and thermal treatments have been applied to reduce excess sludge biomass during the operation of MBRs (8, 23). We very recently reported that a decrease in the feed to microorganism ratio during a simulated rainfall condition suppressed an increase in the sludge biomass in the MBR (20).…”
mentioning
confidence: 99%
“…So far, chemical and thermal treatments have been applied to reduce excess sludge biomass during the operation of MBRs (8, 23). We very recently reported that a decrease in the feed to microorganism ratio during a simulated rainfall condition suppressed an increase in the sludge biomass in the MBR (20).…”
mentioning
confidence: 99%
“…Ventura et al ( 2011) [78] treated real domestic wastewater with a pilot-scale anaerobicanoxic-oxic process, with a submerged membrane in the oxic tank and a thermophilic aerobic digestion reactor. The removal of MLSS, TCOD, BOD, TN, TP, and E. coli by the A 2 O-MBR-TAD process was reported to be nearly 99%, 96%, 70%, 83%, and 99%, respectively.…”
Section: Biological Treatment Processesmentioning
confidence: 99%